2019
DOI: 10.1016/j.bbr.2019.01.007
|View full text |Cite
|
Sign up to set email alerts
|

5-Fluorouracil impairs attention and dopamine release in rats

Abstract: Chemotherapy related cognitive impairment (CTRC; "chemobrain") is a syndrome that is associated with the impairment of various aspects of cognition, including executive function, processing speed, and multitasking. The role of neurotransmitter release in the expression of cognitive impairments is not well known. In this work we employed a newly developed behavioral paradigm to measure attentional shifting, a fundamental component of executive function, in rats treated with 5-fluorouracil (5-FU), a commonly use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 28 publications
(40 reference statements)
0
13
0
1
Order By: Relevance
“…Mice receiving a single injection of doxorubicin had slower glutamate uptake into cells in both the cortex and the dentate gyrus (Thomas et al , ). Similarly, a reduction in dopamine release in the striatum following injections of carboplatin (Kaplan et al , ) or 5‐fluorouracil (Jarmolowicz et al , ) was reported. Serotonin release was also reduced in the raphe nucleus after carboplatin injection (Kaplan et al , ).…”
Section: Introductionmentioning
confidence: 77%
“…Mice receiving a single injection of doxorubicin had slower glutamate uptake into cells in both the cortex and the dentate gyrus (Thomas et al , ). Similarly, a reduction in dopamine release in the striatum following injections of carboplatin (Kaplan et al , ) or 5‐fluorouracil (Jarmolowicz et al , ) was reported. Serotonin release was also reduced in the raphe nucleus after carboplatin injection (Kaplan et al , ).…”
Section: Introductionmentioning
confidence: 77%
“…The results showed that 5-FU impaired attentional shifting. Behavioral outcomes were also compared with the extent of dopamine release measured using fast-scan cyclic voltammetry, which showed decreased dopamine release persisted for a week after the second injection (Jarmolowicz et al 2019).…”
Section: -Fluorouracilmentioning
confidence: 99%
“…Carboplatin was demonstrated to impair dopamine release and uptake in the zebrafish model of chemobrain-related studies ( Field et al, 2018 ). Similarly, a reduction in DA release in the striatum following injections of 5-FU was shown ( Jarmolowicz et al, 2019 ). Treatment with DOX impaired glutamate neurotransmission in the mouse frontal cortex and hippocampus.…”
Section: Central Neurotoxicity: Chemobrainmentioning
confidence: 84%